Laser Additive Manufacturing using directed energy deposition of Inconel-718 wall structures with tailored characteristics. (August 2019) - Jinoop, A.N.; Paul, C.P.; Mishra, S.K.; Bindra, K.S.
Abstract: A process window is developed for fabricating thin walled Inconel 718 (IN718) structures for Laser Additive Manufacturing using Directed Energy Deposition (LAM-DED). In-house developed LAM-DED setup deployed to investigate the effect of process parameters on geometry and quality. The influence of post-heat treatment on microstructure, surface and mechanical properties is also studied. Full factorial experiments are carried out to derive the process window yielding requisite geometry, deposition rate and quality. The optimized process parameters are deployed for thin wall fabrication. The maximum and minimum limits for laser energy per unit length (E) and powder feed rate per unit length (F) are experimentally found to be 210 kJ/m, 105 kJ/m, 12.5 g/m and 4 g/m, respectively for fabricating thin walls of requisite geometry. The fabricated thin walls are observed to be defect free with dendritic microstructure. The microstructural examination of heat-treated samples reveals recrystallized equiaxed grains with reduction in surface tensile residual stress up to 50%, and modified surface topography. The reduction of average hardness by 12%, significant improvement in ductility by 62.5% and improvement in energy storage capacity by 2.4 times are observed during the study. Highlights: Thin wall fabrication using Laser Directed Energy Deposition. Process parameter interactions are investigated. LAM-DED IN718 samples are also subjected to post heat-treatment. Surface, Microstructural, and Mechanical properties studied.